Antiepileptic prophylaxis following severe traumatic brain injury within a military cohort. Issue 2 (24th February 2015) - Cranley, Mark R; Craner, M; McGilloway, E
Abstract : Introduction: Traumatic brain injury increases the risk of both early and late seizures. Antiepileptic prophylaxis reduces early seizures, but their use beyond 1 week does not prevent the development of post-traumatic epilepsy. Furthermore, prolonged prophylaxis exposes patients to side effects of the drugs and has occupational implications. The American Academy of Neurology recommends that antiepileptic prophylaxis should be started for patients with severe traumatic brain injury and discontinued after 1 week. An audit is presented here that investigates the use of prophylaxis in a cohort of military patients admitted to the UK Defence Medical Rehabilitation Centre (DMRC). Methods: Data were collected and analysed retrospectively from electronic and paper records between February 2009 and August 2012. The timing and duration of antiepileptic drug use and the incidence of seizures were recorded. Results: During the study period, 52 patients with severe traumatic brain injury were admitted to the rehabilitation centre: 25 patients (48%) were commenced on prophylaxis during the first week following injury while 27 (52%) did not receive prophylaxis. Only one patient (2%) received prophylaxis for the recommended period of 1 week, 22 patients (42%) received prophylaxis for longer than 1 week with a mean duration of 6.2 months. Two patients (4%) had post-traumatic epilepsy and started on treatment at DMRC. Conclusions: The use of antiepileptic prophylaxis varies widely and is generally inconsistent with evidence-based guidance. This exposes some patients to a higher risk of early seizures and others to unnecessary use of antiepileptics. Better implementation of prophylaxis is required.